Legal Certainty of Land Rights Affected By Natural Disasters - Rachman, Rahmia; Ardiansyah, Erlan (Arena Hukum, 2024)
This research investigates the revitalisation of land rights after natural disasters. Using empirical juridical methods, the study concludes that the revitalisation of land rights in Central Sulawesi, carried out by the provincial government in collaboration with the Ministry of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (Ministry of ATR/BPN) and led by the Head of BPN Central Sulawesi, involves the procurement of land through the use of abandoned land to relocate communities affected by disasters for the public interest. This land procurement is aimed at constructing permanent housing for disaster victims. Although BPN Palu City still recognises the land rights of areas affected by the disaster, these lands can no longer be used as they are located in disaster-prone zones (DPZ). Recipients of permanent housing will receive new certificates for plots of land that have been adjusted to the latest spatial design.